Using Electronic Devices While Driving: Legislation and Enforcement Implications - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Distracted driving is a complex and ever-increasing risk to public safety on roadways. Drivers’ use of electronic devices significantly diverts human attention resources away from the driving task. The enforcement community faces significant challenges as electronic device use has expanded beyond simply texting or talking. Legislation regulating electronic device use while driving is inconsistent in content and implementation.The TRB Behavioral Traffic Safety Cooperative Research Program's BTSCRP Research Report 1: Using Electronic Devices While Driving: Legislation and Enforcement Implications presents the results of an examination of the current state and provincial legislation on electronic device use while driving; evaluates the benefits and impediments associated with enacting, enforcing, and adjudicating electronic device use; and proposes model legislation and educational materials that can be used by relevant stakeholders to enact a law and educate key individuals on the importance of the law.Supplemental the report is a presentation for law enforcement.
Keywords: Transportation and Infrastructure

E-Scooter Safety: Issues and Solutions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Electric scooter (or e-scooter) usage continues to expand worldwide with shared, rented, and privately owned devices. While many communities with e-scooter sharing programs have observed social, health, economic, and environmental benefits of enhanced multimodal travel and having more alternatives to vehicle use, these effects are often accompanied by real and perceived safety challenges.BTSCRP Web-Only Document 5: E-Scooter Safety: Issues and Solutions, from TRB's Behavioral Traffic Safety Cooperative Research Program, seeks to build upon existing research to date, identify key gaps in knowledge and data related to e-scooter behavioral safety, and develop evidence-based guidance that can enhance the coordination of behavioral safety programs and countermeasures with a broader toolbox of approaches to improve safety for all road users.The document is supplemental to BTSCRP Research Report 9: E-Scooter Safety Toolbox.
Keywords: Transportation and Infrastructure

Highway Safety Behavioral Strategies for Rural Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Rural roads have a higher risk of fatality or serious injury than urban roads due to factors such as varying terrain, wildlife, and long distances between services. BTSCRP Web-Only Document 4: Highway Safety Behavioral Strategies for Rural Areas, from TRB's Behavioral Transportation Safety Cooperative Research Program, documents the overall research effort that produced BTSCRP Research Report 8: Highway Safety Behavioral Strategies for Rural and Tribal Areas: A Guide. Supplemental to the document is a PowerPoint presentation that outlines the project.
Keywords: Transportation and Infrastructure

Promoting Older Driver Safety: Guide for State Practices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The large number of baby boomers, who are likely to drive much longer than previous generations, points to an increased need for older-driver safety programs and policies. As state-level agencies charged with providing information and programs on behavioral traffic safety, state highway safety offices (SHSOs) are a logical place for either developing and managing a more extensive older-driver safety program or providing funding and leadership for other agencies that conduct these programs.The TRB Behavioral Traffic Safety Cooperative Research Program's BTSCRP Research Report 4: Promoting Older Driver Safety: Guide for State Practices provides guidance for SHSOs to enhance older driver safety.
Keywords: Transportation and Infrastructure

Improving MPO and SHSO Coordination on Behavioral Traffic Safety: Guide and Toolkit - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
State highway safety offices (SHSOs) manage behavioral traffic safety programs at the state level. At the regional level, metropolitan planning organizations (MPOs) develop safety performance measures and targets. BTSCRP Research Report 7: Improving MPO and SHSO Coordination on Behavioral Traffic Safety: Guide and Toolkit, from TRB's Behavioral Traffic Safety Cooperative Research Program, presents evidence-based information and tools to help improve coordination between SHSOs and MPOs on behavioral traffic safety. Supplemental to the report is a research results document.
Keywords: Transportation and Infrastructure

Combined High-Visibility Enforcement: Determining the Effectiveness - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Highway Traffic Safety Administration defines high-visibility enforcement (HVE) as a universal traffic safety approach designed to create deterrence and change unlawful traffic behaviors. HVE combines highly visible and proactive law enforcement targeting a specific traffic safety issue. Law enforcement efforts are combined with visibility elements and a publicity strategy to educate the public and promote voluntary compliance with the law. BTSCRP Research Report 10: Combined High-Visibility Enforcement: Determining the Effectiveness, from TRB's Behavorial Traffic Safety Cooperative Research Program, provides State Highway Safety Offices (SHSOs) and other safety organizations with an improved understanding of safety outcomes associated with conducting combined HVE. Supplemental to the report are Appendices A and B, which contain the survey given to agencies and a summary of common data collected and metrics used to implement and evaluate HVE campaigns, an Implementation Plan, and Recommendations for additional research.
Keywords: Transportation and Infrastructure

Strategies to Improve State Traffic Citation and Adjudication Outcomes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The ability of state agencies to track citation, adjudication, and disposition data accurately and effectively is essential for the identification and appropriate adjudication of problem drivers and habitual offenders. Efficient data tracking can provide benefits at all steps of the citation-adjudication process, from providing real-time information and safer roadside stops for law enforcement officers to reducing errors and improving transmission speed during the adjudication stage to facilitating data storage and effective analyses following disposition.The TRB Behavorial Transportation Safety Cooperative Research Program's BTSCRP Research Report 5: Strategies to Improve State Traffic Citation and Adjudication Outcomes identifies challenges and barriers to effective citation data tracking along with proven strategies and solutions to address these challenges, with the goal of developing a series of practical and meaningful steps that state highway safety officials could use to implement these strategies.Supplemental to the report is Toolkit for Improving Citation and Adjudication Tracking, which is a PowerPoint presentation with voiceover components. Slides from the toolkit are presented in Appendix D and the script for the voiceover is included in Appendix E.
Keywords: Transportation and Infrastructure

Highway Safety Behavioral Strategies for Rural and Tribal Areas: A Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Roadway fatalities and serious injuries are a significant public health concern in rural and tribal settings. Creating a coalition of interested individuals is part of the Safe System Approach that addresses the high rates of these fatalities and serious injuries. BTSCRP Research Report 8: Highway Safety Behavioral Strategies for Rural and Tribal Areas: A Guide, from TRB's Behavioral Transportation Safety Cooperative Research Program, details this approach, which includes strategies for safer people, safer roads, safer vehicles, safer speeds, and post-crash care. Supplemental to the report are BTSCRP Web-Only Document 4: Highway Safety Behavioral Strategies for Rural Areas and a video that explains how to create a logic model.
Keywords: Transportation and Infrastructure

E-Scooter Safety: Issues and Solutions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Many communities with electric‐scooter (e‐scooter) programs have observed social, health, and environmental benefits; enhanced multimodal connections; and positive economic impacts (such as those derived by delivery services and couriers using e‐scooters and the resultant jobs created). However, these effects are often accompanied by real and perceived safety challenges. The TRB Behavioral Transportation Safety Cooperative Research Program's BTSCRP Research Results Digest 1: E-Scooter Safety: Issues and Solutions is an initial deliverable to a larger ongoing project, in the form of a literature review, that identifies emerging behavioral safety issues arising from the expanding use of e-scooters and summarizes how cities are working to prevent and mitigate injuries.
Keywords: Transportation and Infrastructure

Developing Employer-Based Behavioral Traffic Safety Programs for Drivers in the Workplace - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Work-related traffic crashes remain particularly challenging to address. However, recent research and practice have shown that instilling an awareness of safety and fostering a corporate safety culture supportive of safety may prevent traffic crashes, reduce their frequency, and reduce their severity. The TRB Behavioral Traffic Safety Cooperative Research Program’s BTSCRP Web-Only Document 3: Developing Employer-Based Behavioral Traffic Safety Programs for Drivers in the Workplace reports on a study that reviewed the research literature on employer-based behavioral traffic safety programs, gathered information on existing employer-based behavioral traffic safety programs, identified the relevant behavioral change theories and critical components of existing safety programs, and summarized and analyzed measures of safety program effectiveness. Associated with the document is a summary of measures of effectiveness and a website, BTSCRP WebResource 1: Employer-Based Driver Safety Programs, which provides guidance for planning, implementing, and evaluating employer-based behavioral traffic safety programs.
Keywords: Transportation and Infrastructure

Influence of Infrastructure Design on Distracted Driving - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
While many studies have focused on driver distractions such as cell-phone use, the impact of infrastructure elements on distraction and the extent to which they may cause distraction has not been well studied. Examples include objects that are unusual (such as aesthetic bridges) or confusing (signage or markings) or that require an unusual amount of time to locate (like a specific wayfinding sign among multiple roadside objects).The TRB Behavioral Traffic Safety Cooperative Research Program's BTSCRP Web-Only Document 1: Influence of Infrastructure Design on Distracted Driving provides an opportunity to develop a better understanding of the interaction between the built environment and driver distraction.
Keywords: Transportation and Infrastructure